EFFECTS OF MAGNETIZED WATER ON PHENOLIC COMPOUNDS, LIPID PEROXIDATION AND ANTIOXIDANT ACTIVITY OF MORINGA SPECIES UNDER DROUGHT STRESS - M. M. Hasan; H. F. Alharby; A. S. Hajar; K. R. Hakeem; Y. Alzahrani (Journal of Animal and Plant Sciences, 2018)
Drought stress is one of the major abiotic stresses and serious problem for global crop production. Magnetic water technology is supposed to be an environment-friendly tool used for alleviating abiotic stress in the plants. The current study investigates the application of magnetized or magnetic water (MW) on the two Moringa species (Moringa oleifera and Moringa peregrina) under drought conditions. Magnetic field was applied to magnetize the irrigation water. Both species were exposed to three irrigation regimes including, 100% Field capacity (FC, as Control), 50%Field capacity (FC, as Moderate drought stress) and 20% Field capacity (FC, as Severe drought stress). The pot experiment was conducted in November 2015 under randomized complete block design with three replications in the greenhouse of King Abdulaziz University, Jeddah, Saudi Arabia. The results indicated that the total phenolic compounds, flavonoids, Malondialdehyde (MDA), H O and proline content increased during all the levels of drought stress. In addition, the total 2 2 antioxidant capacity increased during the drought stress in both the species. However, seedlings with magnetic water treatment (MWT) decreased the phenolic and flavonoid compounds, MDA, H O and proline content significantly. The 2 2 M. oleifera and M. peregrina seedlings exposed to drought stress (MS, SS) exhibited 15%, 10% and 21%, 22% decrease in MDA content under MWT. In DPPH assay, the higher antioxidant activity was found in Moringa peregrina (63%) whereas; lower antioxidant activity was found in Moringa oleifera (40%) during drought stress. This study indicates that the MWT helps the plants to become more tolerant during the drought stress by improving their antioxidant capacity. 2 2 Abbreviations: MW=Magnetic water, NW=Normal water, MWT=Magnetic water treatment, MDA=Malondialdehyde, ROS=Reactive oxygen species, OD=Optical density, FC=Field capacity, MS=Moderate drought stress, SS=Severe drought stress, TP=Total phenolic content, TF=Total flavonoid content, TBA=Thiobarbituric acid, H O =Hydrogen 2 2 peroxide, DPPH =1-diphenyl-2-picrylhydrazyl. of the phenolic compounds were identified in drought
Keywords: Flavonoids; H O; MDA; Proline; Reactive oxygen species